The Effect of Digital Leadership and Digital Literacy on Employee Performance at the Cirebon City Education Office - Muhammad Rafli S; Muhamad Alwi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to analyze the influence of digital leadership and digital literacy on the performance of non-teacher structural employees at the Cirebon City Education Office. The research uses a quantitative method with an associative approach. The population in this study is 242 employees, with the research sample determined using probability sampling techniques through the simple random sampling method. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression with the help of SPSS. The results of the study show that digital leadership and digital literacy have a positive and partially significant effect on employee performance. Simultaneously, digital leadership and digital literacy also have a significant effect on the performance of non-teacher structural employees at the Cirebon City Education Office. This research is expected to be a consideration for government agencies in improving employee performance through strengthening digital leadership and increasing digital literacy.